Evaluation of Basic Chemistry Practicum Programs 1 and 2 in Developing Students' Science Process Skills Using the CIPP Model - Nabuasa, Desi Aryanti; Nahadi , Nahadi; Sriyati, Siti; Sopandi, Wahyu; Wiji, Wiji (Universitas Negeri Semarang, 2025)
The Basic Chemistry Practicum I and II are integral components of the chemistry education curriculum, designed to develop students' Science Process Skills (SPS). However, the effectiveness of these programs is often constrained by misalignment between course objectives and practicum modules, insufficient laboratory facilities, and a lack of structured assessment tools. This study aims to evaluate the implementation of these practicum programs using the CIPP (Context, Input, Process, Product) evaluation model. A mixed-methods approach involved document analysis, questionnaires, and checklists. The evaluation was conducted within the Chemistry Education Study Program at a university in East Nusa Tenggara, Indonesia, with participants including 17 third-semester students, one lecturer, and one laboratory assistant. The findings reveal that while the practicum programs contribute to the achievement of learning outcomes, several issues remain. There are inconsistencies between the Semester Learning Plan (RPS) and practicum modules, particularly regarding the sequencing of materials and skill development targets. Students demonstrated moderate mastery of basic and integrated SPS but still required significant support in hypothesis formulation, data interpretation, and understanding of experimental variables. The study also found that instructional strategies and evaluation tools were not fully optimized to foster independent scientific inquiry. To enhance the program's effectiveness, the study recommends revising practicum modules to align more closely with course objectives, integrating interactive media such as virtual simulations, and developing formal assessment instruments to measure SPS development comprehensively. These improvements will better prepare students for complex laboratory work and strengthen their scientific reasoning as future educators.